Vozes de estudantes com deficiência no ensino superior: um olhar para si, para a universidade e para a coletividade - Silva, Suzel Lima da (2024)
The theme of this study addresses the daily lives of students with disabilities and other limiting conditions, enrolled in undergraduate courses at a public university in the interior of the State of Rio Grande do Sul-RS. By covering the relationships established by these subjects in the academic environment, deepening the nuances of their unique daily lives, possibilities of approximation with the meanings and feelings attributed by the experiences present in the narratives are grasped. The objective of the research was to understand how academic daily life enables the development of a feeling of belonging to the collective, reinforcing an inclusive university culture. To the scope given for this research, we add the few scientific findings that encompass people with disabilities and other limiting conditions, to the movement of looking more closely at academic spaces seeking connections and resignifications about their right to be at the University, having preserved the their rights, especially to diversity in everyday life. It is also worth highlighting the pioneering spirit of the chosen institution regarding inclusive practices in the State of Rio Grande do Sul, enhanced by the presence of two undergraduate courses, Special Education and Occupational Therapy, training professionals qualified for inclusive practices. Self-photography, defined by Robert Ziller, was used as a device to encourage students with disabilities and other limiting conditions to revisit the desired spaces arising from a triggering question: which spaces in the academic environment have some meaning or meaning for you? Only students with active enrollment at the University's Headquarters Campus, in undergraduate courses, were included in the study, having obtained acceptance to participate freely in the study, four students. Among the limiting conditions were physical, sensory, visual and auditory issues. Regarding the method, the Oral Life History of Meihy and Holanda was used to account for the narratives based on the meanings attributed and memories recalled from photographic records. Each student defined six most significant images provided by the research that were used as triggers to recover memories during the interview. Among the signs present in the narratives, being a student with a disability or Autism Spectrum Disorder (ASD) at the University studied, in general, presents daily challenges, but which can be given new meaning through actions (broad and specific) to raise awareness of issues linked to acceptance. diversity and combating prejudice in everyday life. Thus, the University can stand out as a space for exercising citizenship and transforming values, promoting research and expanding the debate on the subject, as a first step towards more institutionally adopted inclusive practices. Still being considered an effective tool, welcoming approaches are necessary from the moment of entry, seeking to increase familiarization with the academic environment and its functioning in a more general way, not starting from the limitations arising from the students' health conditions. Thus, it is estimated that it can generate positive expectations in relation to higher education and the adoption of more active attitudes towards the challenges of this phase of the subjects' lives.